2008
DOI: 10.1007/s00267-008-9099-1
|View full text |Cite
|
Sign up to set email alerts
|

Land Degradation on Barren Hills: A Case Study in Northeast Vietnam

Abstract: The term "barren hills" has been a keyword for land degradation in the uplands of Vietnam for over a decade. Nevertheless, the "barren" land is still not adequately ecologically characterized. In this work, we analyze land use-induced changes in vegetation and soil properties along a sequence of barren hills types formed on one physiotope. The study is undertaken in the Bac Kan province, one of the poorest upland regions where livestock plays an important role. A transition from an old-growth laurel forest to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Recent studies in MMSEA suggest that many of the highest reported erosion rates in upland areas are indicative of intensified agriculture systems having some or all of the following characteristics: (1) inadequate erosion-mitigating vegetative cover for several consecutive years or extended periods of time during the rainy season of any one year if more than one crop is planted; (2) the need for repeated weeding; (3) multi-year cropping without a sufficient fallow period during which soil porosity and aggregate stability recover and erodibility decreases; and (4) greater propensity to generate concentrated surface runoff, which contributes to rill erosion and gully formation (e.g., Turkelboom 1999;Ziegler et al 2004a, b;Chaplot et al 2005;Sidle et al 2006;Nguyen et al 2008;Podwojewski et al 2008;Turkelboom et al 2008;Valentin et al 2008). Reduced-fallow systems in Laos, Thailand, and Vietnam experience substantial soil loss from tillage erosion during plot preparation and weeding (Turkelboom et al 1997;Ziegler et al 2007a;Dupin et al 2009).…”
Section: Surface Erosionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent studies in MMSEA suggest that many of the highest reported erosion rates in upland areas are indicative of intensified agriculture systems having some or all of the following characteristics: (1) inadequate erosion-mitigating vegetative cover for several consecutive years or extended periods of time during the rainy season of any one year if more than one crop is planted; (2) the need for repeated weeding; (3) multi-year cropping without a sufficient fallow period during which soil porosity and aggregate stability recover and erodibility decreases; and (4) greater propensity to generate concentrated surface runoff, which contributes to rill erosion and gully formation (e.g., Turkelboom 1999;Ziegler et al 2004a, b;Chaplot et al 2005;Sidle et al 2006;Nguyen et al 2008;Podwojewski et al 2008;Turkelboom et al 2008;Valentin et al 2008). Reduced-fallow systems in Laos, Thailand, and Vietnam experience substantial soil loss from tillage erosion during plot preparation and weeding (Turkelboom et al 1997;Ziegler et al 2007a;Dupin et al 2009).…”
Section: Surface Erosionmentioning
confidence: 98%
“…Nye and Greenland 1965;Bronick and Lal 2005); (5) creation of extensive compacted path networks that generate overland flow frequently (Fig. 2b;Ziegler et al 2000Ziegler et al , 2001aRijsdijk et al 2007b;Turkelboom et al 2008); (6) expansion of processing areas, greenhouse complexes, and other types of compacted surfaces of low infiltrability; (7) excessive surface disturbance across the landscape, such as over-grazing and yearly fires (Nikolic et al 2008); and (8) destruction of natural vegetative buffers capable of infiltrating overland flow (e.g., Rijsdijk et al 2007a;Ziegler et al 2007c;Vigiak et al 2008).…”
Section: Streamflowmentioning
confidence: 99%
“…The barren land category covers about one fifth of the territory of Vietnam. In reality 98% of the land cover in barren areas consists of secondary formations such as grassland, grassland and bushes, scrubland with sparse trees, bamboo, and dense growth of small and medium size trees (dbh=5 to 15 cm; height up to 4 m), which can be associated with the fallow stages of the swiddening cycle (Nicolic et al 2008).…”
Section: Swidden In Southeast Asia-regional and Country Assessments Omentioning
confidence: 99%
“…Repeated shorter fallow cycles can result in severe soil degradation and grassland formation including bamboodominated fallows, particularly if a field is subjected to frequent fires or grazing (Conklin 1959;Durno et al 2007;Nikolic et al 2008). Degradation causes a decline in diversity along with a change in vegetation structure that can result in feedbacks that further erode diversity.…”
Section: The Fallow Phasementioning
confidence: 99%